Cutaneous Manifestations in Patients with End Stage Renal Disease on Hemodialysis - Azar Shirzadian Kebria; Zeinab Aryanian; Amin Choobdar; Roghayeh Akbari (Babol University of Medical Sciences, 2023)
Background: End-stage renal disease (ESRD) is a serious chronic disease that affects many organ systems. Skin manifestations that are commonly seen in ESRD can significantly impair the quality of life in these patients. Early recognition and management of mucocutaneous disorders can improve quality of life and decrease morbidity. This study aimed to evaluate the skin manifestations in ESRD patients undergoing hemodialysis. Methods: In this cross-sectional study 150 patients undergoing hemodialysis in the Nephrology Department of Shahid-Beheshti Hospital in Babol were enrolled. The demographic and clinical data were assessed. Analysis was done by SPSS 22 and significance level was under 0.05. Results: The mean duration of hemodialysis was 8.7 months. The most common skin findings in patients include xerosis 84.7%, pallor 82.7%, pruritus 67.3%, hyperpigmentation 40%, purpura 28%. Skin infections were detected in 36% of patients (fungal 28%, bacterial 10.7%, and viral 5.3%). Nail, hair and mucosal changes were observed among 65.3%, 38% and 17.3% of patients respectively. No significant correlation was detected between skin findings and duration of dialysis. Conclusion: The findings of the present study showed that skin manifestations are highly prevalent among patients with ESRD. Prompt diagnosis and management of the dermatological disorders may improve the quality of life in the affected patients.